Physicochemical and microbiological evaluation of Corrientes artisanal cheese during ripening - Vasek, Olga Myriam (2013)
Fil: Vasek, Olga Myriam. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.